What does it all mean? a very short introduction to philosophy - Nagel, Thomas 1937- (Oxford University Press, 1987)
Most people think about philosophical problems without realizing it. Introducing the uninitiated to the world of philosophical inquiry, this book examines nine philosophical problems fundamental to everyday living. It contains short introduction to the methods of philosophy for those with a taste for abstract ideas and theoretical arguments.